Problems of Business Education in Early Childhood Education ( PAUD ): Systematic Literature Review (SLR) - Nur Kholifah; Ahmad Zainuddin; Mustain Mustain; Subandi Subandi; Aniek Indrawati; Ludi Vishnu Wardana; Angga Martha Mahendra (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2023)
This study aims to determine the implementation problems of instilling entrepreneurial character in early childhood. This study uses the Systematic Literature Review (SLR) method by collecting and analyzing journals related to keywords. Based on the literature study conducted, it was found that the importance of planting and increasing understanding of the concept of entrepreneurship from an early age starting from early childhood education, this implementation needs examples in the form of activities carried out by playing to provide a good understanding of students. Another problem, students are less motivated to look for reference materials related to the material provided. Based on the analysis of learning tools, the entrepreneurship material being taught is still not sustainable so that the expected competencies are not clear. In addition, learning activities are still centered on the teacher. The results of the analysis of reference books to see the contents of the material, especially the main economic activity material. How the material is presented, examples, and practical implementation in accordance with the syllabus of existing subject matter. After the basic economic activity reference books are reviewed as teaching materials in accordance with the learning tools that have been developed.